Peran Nazir Dalam Pendayagunaan Tanah Wakaf Produktif Masjid Jami’ Gresik. - Sofyan Tsauri, Muchammad; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2019)
The purpose of this research is to find out how Na?ir's role is in the utilization of productive waqf land in the Jami Gresik mosque. This study uses a descriptive qualitative approach. The data used by the author are primary and secondary data. Data collection techniques in this study using interviews, observation and documentation. The results of this study indicate that the Takmir of Jami Mosque 'Gresik as Na?ir of Jami Mosque' Gresik has a role as a collector of funds from the community, Distributing funds obtained from the community for funding school, mosque operational, donation for orphan, and reporting on funds distributed to the public. The Na?ir Mosque of Jami 'Gresik was also analyzed with eight professional Na?ir indicators proposed by the ministry of religion such as Skill, Attitude, Good Integrity, High Work ethic, Implementing Operational Standard, Creativity, Leadership and Networking